2004
DOI: 10.3354/dao059069
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus (WSSV) detected by PCR in rotifers and rotifer resting eggs from shrimp pond sediments

Abstract: White spot syndrome virus (WSSV) was detected by PCR-dot blot hybridization in rotifer resting eggs from shrimp Penaeus chinensis culture-pond sediments. It was also detected in rotifers hatched from those eggs. Surface disinfection before analysis indicated that WSSV was probably present within the resting eggs. Results suggested that rotifer resting eggs may be an overwintering reservoir for WSSV in shrimp ponds. KEY WORDS: Rotifer resting eggs · White spot syndrome virus · Transmission routeResale or republ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 10 publications
0
40
0
6
Order By: Relevance
“…At least 18 cultured and/or wild penaeid shrimp (Park et al, 1998), eight caridean species (Pramod-Kiran et al, 2002), seven species of lobster (Rajendran et al, 1999), seven species of crayfish (Edgerton, 2004), 38 crab species (Yoganandhan et al, 2003) six non-decapod crustacean species (Hossain et al, 2001), members of the phyla Chaetognata and Rotifera (Yan et al, 2004), polychaete worms (Supak et al, 2005) and some aquatic insect larva (Ramírez-Douriet et al, 2005) have been found susceptible to the virus. Histopathological observations during WSV infection in brief is available regarding shrimp species such as Penaes monodon (Durand et al, 1997;Wang et al, 1999Wang et al, , 2000Mishra and Shekhar, 2005) Litopenaeus vannamei and Marsupenaeus japonicus (Lu et al, 1997;Lightner et al, 1998;Escobedo-Bonilla et al, 2007;Perez et al, 2005;Pantoja and Lightner, 2003), species of Crabs (Kanchanaphum et al, 1998;Kou et al, 1998) and lobster (Rajendran et al, 1999;Wang et al, 1998;Jiravanichpaisal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…At least 18 cultured and/or wild penaeid shrimp (Park et al, 1998), eight caridean species (Pramod-Kiran et al, 2002), seven species of lobster (Rajendran et al, 1999), seven species of crayfish (Edgerton, 2004), 38 crab species (Yoganandhan et al, 2003) six non-decapod crustacean species (Hossain et al, 2001), members of the phyla Chaetognata and Rotifera (Yan et al, 2004), polychaete worms (Supak et al, 2005) and some aquatic insect larva (Ramírez-Douriet et al, 2005) have been found susceptible to the virus. Histopathological observations during WSV infection in brief is available regarding shrimp species such as Penaes monodon (Durand et al, 1997;Wang et al, 1999Wang et al, , 2000Mishra and Shekhar, 2005) Litopenaeus vannamei and Marsupenaeus japonicus (Lu et al, 1997;Lightner et al, 1998;Escobedo-Bonilla et al, 2007;Perez et al, 2005;Pantoja and Lightner, 2003), species of Crabs (Kanchanaphum et al, 1998;Kou et al, 1998) and lobster (Rajendran et al, 1999;Wang et al, 1998;Jiravanichpaisal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The well-studied insect errantiviruses from the gypsy clade were shown to have acquired their env region from baculoviruses, and the env regions of the nematode Cer and Tas retroviruses were acquired from a phlebovirus and a herpesvirus, respectively. So far, only one virus from aquatic invertebrates has been sequenced, a large DNA virus that can pass between rotifer and shrimp hosts (Yan et al, 2004). Although its ORFs do not reveal similarities with bdelloid env-like genes, additional viruses inhabiting aquatic invertebrates will hopefully be characterized in the future (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Macrobrachium rosenbergii nodavirus (MrNV; the causative agent of white tail disease) and extra small virus (XSV) can be vertically transmitted (Sudha ka -ran et al 2007). Rotifers naturally exposed to sediments with WSSV passed the virus to their eggs (Yan et al 2004), and the virus appears to use vertical transmission in brine shrimp as well (Li et al 2003). Infectious hypodermal and hemato poietic necrosis virus (IHHNV) of shrimp uses vertical transmission in hosts that survive the acute stages of infection (Motte et al 2003).…”
Section: Discussionmentioning
confidence: 99%